Theories of Business Fluctuations - Persons, Warren M. (Quarterly Journal of Economics, 1926)
Definition of the phrases "business fluctuations, " 94; "business cycle, " 95; "periodic cycle, " 95. — Concept of normal, 96. — Old and new meanings attached to "commercial crisis, " 98. — Classification of the theories according to emphasis placed on causes, 99. — Extracts from writers emphasizing factors other than economic institutions, 104. — Extracts from writers emphasizing economic institutions, 109.